Production and Characterization of Antioxidative Hydrolysates and Peptides from Corn Gluten Meal Using Papain, Ficin, and Bromelain - Ruijia Hu; Gengjun Chen; Yonghui Li (Molecules, 2020)
There has been a growing interest in developing natural antioxidants with high efficiency and low cost. Bioactive protein hydrolysates could be a potential source of natural and safer antioxidants. The objectives of this study were to hydrolyze corn gluten meal using three plant-derived proteases, namely papain, ficin, and bromelain, to produce antioxidative hydrolysates and peptides and to characterize the antioxidant performances using both chemical assays and a ground meat model. The optimum hydrolysis time for papain was 3 h, and for ficin and bromelain was 4 h. The hydrolysates were further separated by sequential ultrafiltration to 5 hydrolysate fractions named F1 to F5 from low molecular weight (MW) (<1 kDa) to high MW range (>10 kDa), which were further characterized for TPC, free radical scavenging capacity against DPPH and ABTS, and metal chelating activity. The fraction F4 produced by papain (CH-P4), F1 produced by ficin (CH-F1), and F3 produced by bromelain (CH-B3) showed the strongest antioxidant activity and yield, respectively. These three fractions were incorporated into ground pork to determine their inhibition effects on lipid oxidation during a 16-day storage period. The inhibition effect was enhanced with the addition of higher amount of hydrolysate (e.g., 1000 vs. 500 mg/kg). The CH-P4 reduced lipid oxidation in ground meat by as much as 30.45%, and CH-B3 reduced oxidation by 27.2% at the same level, but the inhibition was only 13.83% with 1000 mg/kg of CH-F1. The study demonstrated that CGM protein hydrolysates and peptides could be used as naturally derived antioxidant in retarding lipid oxidation and improving product storage stability.